2022
DOI: 10.3390/metabo12020139
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolomic Changes Accompanying Albuminuria Remission following Gastric Bypass Surgery for Type 2 Diabetic Kidney Disease

Abstract: In the Microvascular Outcomes after Metabolic Surgery randomised clinical trial (MOMS RCT, NCT01821508), combined metabolic surgery (gastric bypass) plus medical therapy (CSM) was superior to medical therapy alone (MTA) as a means of achieving albuminuria remission at 2-year follow-up in patients with obesity and early diabetic kidney disease (DKD). In the present study, we assessed the urinary 1H-NMR metabolome in a subgroup of patients from both arms of the MOMS RCT at baseline and 6-month follow-up. Whilst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The post-DMT urinary metabolome was characterised by increased abundance of PPARα-responsive metabolites involved in nicotinamide metabolism (1-methylnicotinamide, nicotinamide N-oxide, and nicotinurate). Notably, changes in the urinary excretion of metabolites reflective of host-gut bacterial co-metabolism, which are well described following RYGB and associated with beneficial metabolic and renal effects of the procedure [ 102 104 ], were not pronounced following DMT.…”
Section: Resultsmentioning
confidence: 99%
“…The post-DMT urinary metabolome was characterised by increased abundance of PPARα-responsive metabolites involved in nicotinamide metabolism (1-methylnicotinamide, nicotinamide N-oxide, and nicotinurate). Notably, changes in the urinary excretion of metabolites reflective of host-gut bacterial co-metabolism, which are well described following RYGB and associated with beneficial metabolic and renal effects of the procedure [ 102 104 ], were not pronounced following DMT.…”
Section: Resultsmentioning
confidence: 99%
“…It's reported that in patients with acute kidney injury (AKI), 4-acetamidobutanoate increased 12-fold [ 37 ], and its levels significantly increased in patients with morbid hypertension [ 38 ]. Similarly, alpha-hydroxyisovalerate, an organic acid related to branched-chain amino acid metabolism, has been linked with liver injury [ 39 ], diabetic nephropathy [ 40 ], and Maple Syrup Urine Disease [ 41 ]. These findings might help in predicting the prognostic features of OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased levels of the Krebs cycle intermediates citrate and malate further support a high activity in oxidative mitochondrial metabolism [31]. However, we cannot rule out that changes in these intermediates reflect RYGB‐associated changes in renal function [32].…”
Section: Discussionmentioning
confidence: 99%